Macroeconomic reforms and regional integration southern Africa - Mataya, Charles (International Food Policy Research Institute, 1997)
The economic crises of the 1970s, in many cases associated with inappropriate domestic macroeconomic policies, droughts, and a number of unfavorable external factors, prompted several African countries to implement structural reforms and adjustment policies in the 1980s aimed at restoring external and internal equilibria. Adjustment programs have in almost all countries attempted to eliminate distortion, often said to prevent efficient allocation of resources. These programs generally included reforms to establish a market-determined exchange rate; bring fiscal deficits under control and rationalize public investment; and liberalize trade (for example, by abolishing licenses and quantitative restrictions) and tariff policy (by moving toward low and uniform tariff rates), liberalize agricultural prices and marketing, deregulate internal prices, and similar measures. They also sought to improve financial sector policy (to achieve competitive returns on financial assets, increase the marginal productivity of capital, and boost the saving rate); improve the efficiency of public enterprises and labor markets (to enhance the mobility of goods and labor and to make prices and wages more flexible); and improve the coverage and quantity of social services.